2003
DOI: 10.1590/s0034-70942003000200004
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo entre bupivacaína a 0,5% e mistura enantiomérica de bupivacaína (S75-R25) a 0,5% em anestesia peridural

Abstract: RESUMOGonçalves RF, Lauretti GR, Mattos AL -Estudo Comparativo entre Bupivacaína a 0,5% e Mistura Enantiomérica de Bupivacaína (S75-R25) a 0,5% em Anestesia Peridural Justificativa e Objetivos -A mistura enantiomérica de bupivacaína (S75-R25) Background and Objectives -A bupivacaine formulation containing 25% of R(+) and 75% of S(-) isomer has been used because its anesthetic properties with less toxicity than the racemic bupivacaine. This study aimed at evaluating the racemic bupivacaine as compared to B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
(25 reference statements)
0
8
0
7
Order By: Relevance
“…Although the in vitro studies suggest that the motor blockade of both isomers of bupivacaine is similar 9 , a recent study observed that sodium channels blockade is more potent with the dextrorotatory isomer than the levorotatory isomer 10 justifying the weaker motor blockade of enantiomeric excess bupivacaine observed in the present study. Similarly, a clinical study comparing 0.5% bupivacaine with 0.5% enantiomeric excess bupivacaine (S75-R25) in 44 patients undergoing epidural block for vascular or orthopedic surgeries of the lower limbs concluded that the degree of the motor blockade was greater in the group that received 0.5% of bupivacaine 11 . Skeletal muscle blockade is one of the most undesirable effects during labor analgesia due to the increased risk of instrumental delivery, longer duration of labor and maternal dissatisfaction 6,12 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the in vitro studies suggest that the motor blockade of both isomers of bupivacaine is similar 9 , a recent study observed that sodium channels blockade is more potent with the dextrorotatory isomer than the levorotatory isomer 10 justifying the weaker motor blockade of enantiomeric excess bupivacaine observed in the present study. Similarly, a clinical study comparing 0.5% bupivacaine with 0.5% enantiomeric excess bupivacaine (S75-R25) in 44 patients undergoing epidural block for vascular or orthopedic surgeries of the lower limbs concluded that the degree of the motor blockade was greater in the group that received 0.5% of bupivacaine 11 . Skeletal muscle blockade is one of the most undesirable effects during labor analgesia due to the increased risk of instrumental delivery, longer duration of labor and maternal dissatisfaction 6,12 .…”
Section: Resultsmentioning
confidence: 99%
“…Esses resultados são conflitantes com os encontrados no presente estudo, no qual o bloqueio motor foi mais intenso nas gestantes que utilizaram bupivacaína racêmica (S50-R50) do que nas que utilizaram bupivacaína em excesso enantiomérico de 50% (S75-R25) nas duas diferentes concentrações. Apesar de estudos in vitro sugerirem que os dois isômeros da bupivacaína são eqüipotentes em determinar bloqueio motor 9 , trabalho publicado mais recentemente observou que a forma dextrógira é mais potente do que a forma levógira em inibir canais de sódio 10 , o que justifica o menor bloqueio motor observado nessa pesquisa com a bupivacaína com maior concentração do isômero S. Da mesma forma, um estudo clínico comparando a bupivacaína a 0,5% com a mistura enantiomérica de bupivacaína (S75-R25) a 0,5% em 44 pacientes submetidos à anestesia peridural para procedimentos vasculares ou ortopédicos dos membros inferiores concluiu que o grau de bloqueio motor foi mais intenso no grupo bupivacaína a 0,5% quando comparado com a mistura enantiomérica de bupivacaína (S75-R25) a 0,5% 11 . O bloqueio da musculatura esquelética é um dos efeitos mais indesejáveis durante a analgesia de parto, pelo risco de aumento da freqüência de parto instrumental, maior duração do trabalho de parto e insatisfação materna 6,12 .…”
Section: Após a Aprovação Do Comitê De éTica Em Pesquisa Em Seres Humunclassified
“…Aadministração de S75-R25 em camundongos potencializou a intensidade e prolongou o tempo de analgesia quando comparada à S50-R50, especialmente nas menores concentrações (0,125% e 0,25%). A literatura relata que a S75-R25 proporciona boas condições para a realização do ato anestésico-cirúrgico com adequados bloqueios motor e sensorial [22][23] prolongando a analgesia pós-operatória em relação à S50-R50 24 . Além disso, a S75-R25 mostrou-se formulação mais segura que a S50-R50 água, facilitando o acesso de anestésicos hidrofóbicos, como S50-R50 e S75-R25, ao local de ação.…”
Section: Métodounclassified
“…A levobupivacaína proporciona menor bloqueio motor do que a mistura racêmica 7,[14][15][16][17] , por esta razão, talvez houvesse um interesse na adição de pequena quantidade do isômero dextrógiro para . A indústria nacional comercializou este produto e, desde então, ele tem larga utilização em nosso meio, sendo reputado, inclusive, por menor toxicidade.…”
Section: Discussionunclassified